Work in America: 1950 to 2019 - Giuseppe Ruggeri (Zenodo, 2022)
This paper uses a consistent methodology to estimate average weekly hours of work in the United States in 1950 and 2019. It also reviews a number of studies that cover parts of the same period. Making adjustments where possible to reduce methodological differences, this review identifies three sub-periods: 1950 to 1980, when working hours declined; 1980 to 1990, when working hours rose; and 1990 to 2019, when working hours remained constant. It also briefly discusses the importance of a variety of factors affecting the different response by working hours to the growth of real GDP and labor productivity during the first and last sub-periods.
Keywords: J01; 330; work in america